DERMATOGLYPHICS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS FROM SANTA IZABEL HOSPITAL IN SALVADOR–BRAZIL AND HEALTHY INDIVIDUALS. (Fiep Bulletin - online, 2011)
The study objective was to compare the results of the dermatoglyphic characteristic of patients with systemic lupus erythematosus (SLE) from Santa Izabel Hospital in Salvador-Brazil with healthy individuals volunteers from a specific Fitness Center in Salvador-Brazil. For this purpose, the Cummins and Midlo (1961) DERMATOGLYPHICS method was used. 27 women were analyzed, being 14 women with SLE with mean of 39±12.65 years old and 13 healthy women with mean of 41±4.13 years old. The variables were compared by the Mann-Whitney no parametric test. For the statistic test, a significative p-value of (p< 0,05) was considered. The analyzed variables have shown the following mean and deviation pattern for healthy women: D10 (10.92±0.90); TRC (125.92±50.38); ATDD angle (42.08±3.68) and ATDE (41.69±2.81), 'a-b' triradius right hand (69.00±13.53) and (68.61±14.90) left hand. For women with SLE, the following pattern: D10 (11.93±38.32); TRC (115.71±38.32); ATDD angle (43.64±5.3) and ATDE (42.86±4.9), 'a-b' triradius right hand (50.00±7.05) and (50.07±6.45) left hand. The obtained results haven't shown a significative statistic difference among the studied groups in the variables: drawn type Arch (A) p=0.2298; drawn type Loop (L) p=0.7516 and drawn type Whorl (W) p=0.3809; D10 p=0.3433; TRC p=0.5442; ATDD angle p=0.5754 and ATDE p=0.865, but in the ab triradius variable from both hands, the study has shown a significative right hand p of p=0.0009 and for left hand p of p=0.0011. It can be concluded from this study, based upon results which was found in(a-bD) and (a-bE) triradius, that the use of the DERMATOGLYPHICS method helps the diagnosis for patients with SLE corroborating with works which were done previously and had obtained similar results and confirm the existence of the relationship between the genetic factor and the SLE.
Keywords: systemic lupus erythematosus; disease; DERMATOGLYPHICS